Bilateral Pleural Effusion in a Patient with an Extensive Extramedullary Hematopoietic Mass - Luo, Yun (Hindawi Publishing Corporation, 2013)
We present a 56-year-old woman with bilateral pleural effusions, widespread enlarged lymph nodes, and soft tissue masses located within the renal pelvis. The initially working diagnosis was tuberculosis and lymphoma. Further pathological examination of the lymph node biopsy confirmed a diagnosis of extramedullary hematopoiesis, and a bone marrow biopsy revealed myelofibrosis. Unlike common treatment options such as radiotherapy and/or surgery, intrathoracic cisplatin and dexamethasone for the treatment of pleural effusions secondary to extramedullary hematopoiesis demonstrated an improvement in feasibility and efficacy in the present case.